Concept of Establishing a Legal Entity for Tabarru’ Funds as a Stakeholder Representative of Sharia Insurance Participants - Afifullah, Muhamad; Winanti, Atik; Wati, Diani Sadia (Journal of Modern Islamic Studies and Civilization, 2025)
This study explores establishing a legal entity as a representative body for participants in Islamic insurance, in light of current Indonesian regulations and the fatwas and guidelines issued by the National Sharia Board of the Indonesian Council of Ulama (DSN-MUI). Using a normative juridical method with statutory, comparative, and conceptual approaches, this research draws on primary legal materials—including statutory laws and DSN-MUI fatwas—and secondary sources such as scholarly literature and credible legal documents. The proposed legal entity aims to represent the collective ownership of Islamic insurance participants. It suggests forming an internal body comprised of participant representatives from various regions, modeled after the Badan Perwakilan Anggota (Member Representative Body) in mutual insurance. This initiative is intended to enhance participant rights and address conflicts of interest arising from Islamic insurance companies' dual role as both fund managers and supervisors. Despite its potential, forming such an internal legal body faces practical and legal obstacles, including financing issues, representative selection criteria, operational efficiency, and the absence of specific regulatory support. Furthermore, the existing authority of the Sharia Supervisory Board (DPS) is limited to Sharia compliance oversight. As a viable alternative, appointing an Independent Commissioner to represent participants is recommended. This solution is grounded in existing laws, such as the Company Law, Insurance Law, UUP2SK, and relevant OJK regulations. It can be enhanced by establishing a Dana Tabarru’ Funds committee under Article 121(1) of the Company Law to ensure stronger accountability and protection of participants’ interests.